The importance and involvement of landscape architecture in the green building index (GBI) practice / Norhanis Diyana Nizarudin, Mohd Ramzi Mohd Hussain and Izawati Tukiman - Nizarudin, Norhanis Diyana; Mohd Hussain, Mohd Ramzi; Tukiman, Izawati (2012)
This paper fundamentally discusses on the importance of the Landscape Architecture scope of works and professionalism in the application of the GBI. It sets out to investigate how the particular scope of works as well as the involvement of the Landscape Architecture professionals in the organization is being considered throughout the GBI practice. According to past researches, there are several professions that are mostly active in the green building and the GBI projects. The architects took the first place for the most involved and active profession during the design process of the green buildings followed by the mechanical, electrical, structural and civil engineers; the interior designers and the quantity surveyors. Based on that research evidence, inactive involvement of the Landscape Architecture professionals in the GBI practice is seen as an issue whereby in consequence, the landscape architecture professionals are not put in place together with other allied professions in the green building team. The study basically used questionnaire survey and semi-structured interviews, apart from secondary data collection obtained from the literature review and document analysis. From the evaluation of the survey and interviews, the study found that the Landscape Architecture is a very important field in the green building and the GBI development. It was found that the landscape design should be included from the very beginning of conceptual design stage in order to determine the right, sufficient and proper placement of the green areas. It also supported the role of the Landscape Architects as being important to be imposed in the GBI practice. Landscape Architects should be included in the green building design team to integrate the comprehensive knowledge of landscape design with other professionals in order to lead towards a multidisciplinary approach.